The Motion Transform: a new Motion Compensation Technique - Armitano, Robert M.; Florencio, Dinei; Schafer, Ronald W. (ICASSP, 1996)
Motion estimation plays an important role in video coding schemes by removing temporal redundancies that exist in image sequences. Motion information that is required in motion compensated prediction is transmitted as side information, as in forward motion estimation, or can be computed at the receiver in backward motion estimation. The former method has the advantage of more accurate prediction but, suffers in that the motion information is transmitted as side information. We introduce the Motion Transform (MT), a new motion estimation and compensation technique that does not require the transmission of motion vectors yet, performs well under a variety of conditions. In the proposed method, motion information is obtained in a bottom-up hierarchical fashion using a two-dimensional wavelet-like decomposition.